SISTEM PENYIRAMAN OTOMATIS MENGGUNAKAN RTC (REAL TIME CLOCK) BERBASIS MIKROKONTROLER ARDUINO MEGA 2560 PADA TANAMAN MANGGA HARUM MANIS BULELENG BALI - Rahardjo, Pratolo (Jurnal SPEKTRUM, 2021)
Along with technological developments, various technological innovations have begun to emerge that can be applied to facilitate individual or group work. One of them is the use of appropriate technology, namely the use of technology in a field that can provide real benefit. Researchers designed an automatic watering system using RTC (Real time clock) based on the Arduino Mega 2560 microcontroller. This watering system works automatically based on a specified watering schedule according to the user's wishes. Users can set the watering time easily because the system is equipped with a keypad. Based on the results of tests carried out, the watering process occurs, when the time displayed on the LCD is the same as the time setting given. Long watering duration of approximately 1 minute.